Piccoli gesti, piccole cose. Abitare, navigare, farsi comunità a bordo della barca a vela Raj - Cinzia Settembrini (Archivio Antropologico Mediterraneo)
Considering the Raj as a social unit, the present contribution reflects upon the constituent relation between the materiality/spatiality of the sailboat, and the multiple processes of subjectification of the hermenautic crew. Accordingly, the article considers materiality as being a core element in the mutual co-constitution of objects and subjects. It also accounts for the daily micro-practices that shape and frame knowledge-circulation and forms of cohabitation on board, emphasizing the co-existence of multiple practices of care but also of constant interpersonal tensions and negotiations. Finally, the article strives to expand the concept of ‘nautical knowledge’ by reflecting upon the mutual implication and contingent articulation of practices of ‘inhabiting’ and ‘sailing’ on board. The goal is thus to analyze the boat as a space of technical and relational apprenticeship and as a moving repository of multiple social affects and meanings.